Identification and Management of Plant Parasitic Nematodes Associated with Walnut (Juglans Regia L.) in Abbottabad - Nadia Saeed, Seema Anar, Qasim Saeed, Khalid Usman, Javed Ahmed Ujjan, Fahim Haider Jamali, Shams Ud Din, Muhammad Idrees, Muhammad Sajid, Iftikhar Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Methods: Soil samples from walnut trees were collected from different localities were processed by using Bearmann funnel techniques. Several nematode species were identified including Meloidogyne incognita, Helicotylenchus dihystera, Psilenchus hilarulus, Tylenchus sp. and Helicotylenchus vulgaris. Findings & Practical implication: Management of plant parasitic nematodes by using castor oil cakes (8kg/tree), cow dung (8 kg/tree) and duck manure (8kg/tree) showed that population was declined after application. Plant growth and yield was also improved. Data plotted in histogram graphs and t-test showed that p values were found significant. Conclusion: The mean and S.D values of initial population, 3 month, 6 month and 12 month for castor oil cakes are 116 ± 1.2, 84 ± 1.0, 60 ± 1.0, 42 ± 0.6, for cow dung 127 ± 5.7, 110 ± 2.4, 87 ± 2.4, 73 ± 1.3 and for duck manure 108 ± 2.4, 92 ± 1.0, 69 ± 0.5, 45 ± 1.0. Keywords: Phytonematodes, walnut, castor oil, cow dung, duck manure.